2015
DOI: 10.1002/2015gl065493
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the contrasting North Atlantic Oscillation anomalies of the winters of 2010 and 2014

Abstract: The present study investigates the two contrasting winters of 2010 and 2014 during which the North Atlantic Oscillation (NAO) was mainly negative and positive, respectively. In the North Pacific, contrasting anomalies were also present, with a straight zonal Pacific jet in 2010 and a strong poleward deviation of the Pacific jet in its exit region in 2014. Using reanalysis data sets and adopting a nonlinear initial‐value approach with a quasi‐geostrophic model, we show that the Pacific‐North American anomalies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…In contrast, composites of C‐ and N‐jet days (Figure b, c, shading) show two distinct jets as in the climatology (blue contours), with the North Atlantic jet positioned poleward of 45 ° N and cleanly separated from the African subtropical jet at approximately 18 ° N. The M‐jet composite (Figure d) gives the impression of a relatively broad, weak jet, but this is in fact an artifact of zonally averaging over a complex jet structure. The S‐jet composite resembles the 2010 winter‐mean jet (Figure a, orange contours), which was also anomalously zonal and southward‐shifted (e.g., Harnik et al ., ; Rivière and Drouard, ).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…In contrast, composites of C‐ and N‐jet days (Figure b, c, shading) show two distinct jets as in the climatology (blue contours), with the North Atlantic jet positioned poleward of 45 ° N and cleanly separated from the African subtropical jet at approximately 18 ° N. The M‐jet composite (Figure d) gives the impression of a relatively broad, weak jet, but this is in fact an artifact of zonally averaging over a complex jet structure. The S‐jet composite resembles the 2010 winter‐mean jet (Figure a, orange contours), which was also anomalously zonal and southward‐shifted (e.g., Harnik et al ., ; Rivière and Drouard, ).…”
Section: Resultsmentioning
confidence: 91%
“…Repeating the analyses performed on the synoptic S‐jet for the 2010 winter, we find a consistent picture of a merged jet that is more thermally driven and less eddy‐driven. This allows us to link previous studies that suggested key roles for tropical heating (Harnik et al ., ) and cyclonic wave breaking (Rivière and Drouard, ) for this particular winter season. Enhanced thermal driving from the tropical Pacific during the 2010 winter is similar to, though stronger than, the anomalies in the S‐jet composite (Figure c,a).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Finally, according to dynamical systems metrics, the same winter was very low dimensional (and hence predictable). None of these approaches is incorrect, and indeed they are only apparently inconsistent: a more intense eddydriven jet means more eddy momentum deposit and hence more wave-breaking activity (Rivière and Drouard 2015). The different viewpoints discussed above therefore provide complementary (and sometimes overlapping) information.…”
Section: Future Perspectives and Chal-lenges In The Fieldmentioning
confidence: 99%